A Temporal Activity of CA1 Neurons Underlying Short-Term Memory for Social Recognition Altered in PTEN Mouse Models of Autism Spectrum Disorder - Chai, An-Ping; Chen, Xue-Feng; Xu, Xiao-Shan; Zhang, Na; Li, Meng; Li, Jin-Nan; Zhang, Lei; Zhang, Dai; Zhang, Xia; Mao, Rong-Rong; Ding, Yu-Qiang; Xu, Lin; et al. (Frontiers in Cellular Neuroscience, 2021)
Memory-guided social recognition identifies someone from previous encounters or experiences, but the mechanisms of social memory remain unclear. Here, we find that a short-term memory from experiencing a stranger mouse lasting under 30 min interval is essential for subsequent social recognition in mice, but that interval prolonged to hours by replacing the stranger mouse with a familiar littermate. Optogenetic silencing of dorsal CA1 neuronal activity during trials or inter-trial intervals disrupted short-term memory-guided social recognition, without affecting the ability of being sociable or long-term memory-guided social recognition. Postnatal knockdown or knockout of autism spectrum disorder (ASD)-associated phosphatase and tensin homolog (PTEN) gene in dorsal hippocampal CA1 similarly impaired neuronal firing rate in vitro and altered firing pattern during social recognition. These PTEN mice showed deficits in social recognition with stranger mouse rather than littermate and exhibited impairment in T-maze spontaneous alternation task for testing short-term spatial memory. Thus, we suggest that a temporal activity of dorsal CA1 neurons may underlie formation of short-term memory to be critical for organizing subsequent social recognition but that is possibly disrupted in ASD.